The progress of induced pluripotent stem cells derived from pigs: a mini review of recent advances - Neira, Jaime A.; Conrad, J. Vanessa; Rusteika, Margaret; Chu, Li-Fang (Frontiers in Cell and Developmental Biology, 2024)
Pigs (Sus scrofa) are widely acknowledged as an important large mammalian animal model due to their similarity to human physiology, genetics, and immunology. Leveraging the full potential of this model presents significant opportunities for major advancements in the fields of comparative biology, disease modeling, and regenerative medicine. Thus, the derivation of pluripotent stem cells from this species can offer new tools for disease modeling and serve as a stepping stone to test future autologous or allogeneic cell-based therapies. Over the past few decades, great progress has been made in establishing porcine pluripotent stem cells (pPSCs), including embryonic stem cells (pESCs) derived from pre- and peri-implantation embryos, and porcine induced pluripotent stem cells (piPSCs) using a variety of cellular reprogramming strategies. However, the stabilization of pPSCs was not as straightforward as directly applying the culture conditions developed and optimized for murine or primate PSCs. Therefore, it has historically been challenging to establish stable pPSC lines that could pass stringent pluripotency tests. Here, we review recent advances in the establishment of stable porcine PSCs. We focus on the evolving derivation methods that eventually led to the establishment of pESCs and transgene-free piPSCs, as well as current challenges and opportunities in this rapidly advancing field.